Association between the physical stability of flurbiprofen suspension and the interaction of HPMC/SDS - Hongyu Wang; Yiwei Sun; Baixue Yang; Sanming Li (Elsevier, 2018)
The anionic surfactant sodium dodecylsulfate (SDS) has improved the physical stability of flurbiprofen (FBP) suspension, which was suspended by 0.2% (w/v) hydroxypropylmethyl cellulose (HPMC, K4M). Therefore, the physical stability of FBP suspensions and the interaction of HPMC/SDS were studied, and a certain association between them was revealed. The anti-solvent precipitation method was used to prepare suspensions. The apparent drug concentration from different sites was evaluated to get the dispersion of drug actually. The process of flocculation and deflocculation with the addition of SDS was caught by analyzing the morphology of the suspended particles. The physical stability of the FBP suspensions was characterized mainly by measuring the re-dispersion time, the zeta potential and particle size. Meanwhile, conductivity measurements were carried out to obtain the characteristic concentrations of SDS in HPMC/SDS system. The viscosities, the abilities for improving the solubility and wettability of FBP in the separate and mixed HPMC/SDS solutions were also contrasted respectively. The suspensions prepared with HPMC/SDS possessed better physical stability. The suspensions were uniform when the concentration of SDS was between the critical adsorption concentration (CAC) and the polymer saturation point (PSP). After PSP, the uniformity became worse and worse until the SDS was enough to form a deflocculation state. Besides, the re-dispersion time of FBP suspensions was longest when the concentration of SDS around CAC and shorter by shorter after the critical micelle concentration (CMC). The article provided a new sight on the relation between the interaction of excipient matrix and pharmaceutical preparations.